Circular economyeast: Saccharomyces cerevisiae as a sustainable source of glucans and its safety for skincare application - Sousa, Pedro; Tavares-Valente, Diana; Pereira, Carla F.; Pinto-Ribeiro, Inês; Azevedo-Silva, João; Madureira, Raquel; Ramos, Óscar L.; Pintado, Manuela; Fernandes, João; Amorim, Manuela (International journal of biological macromolecules, 2024)
Glucans, a polysaccharide naturally present in the yeast cell wall that can be obtained from side streams generated during the fermentation process, have gained increasing attention for their potential as a skin ingredient. Therefore, this study focused on the extraction method to isolate and purify water-insoluble glucans from two different Saccharomyces cerevisiae strains: an engineered strain obtained from spent yeast in an industrial fermentation process and a wild strain produced through lab-scale fermentation. Two water-insoluble extracts with a high glucose content (> 90 %) were achieved and further subjected to a chemical modification using carboxymethylation to improve their water solubility. All the glucans' extracts, water-insoluble and carboxymethylated, were structurally and chemically characterized, showing almost no differences between both yeast-type strains. To ensure their safety for skin application, a broad safety assessment was undertaken, and no cytotoxic effect, immunomodulatory capacity (IL-6 and IL-8 regulation), genotoxicity, skin sensitization, and impact on the skin microbiota were observed. These findings highlight the potential of glucans derived from spent yeast as a sustainable and safe ingredient for cosmetic and skincare formulations, contributing to the sustainability and circular economy.